2011
DOI: 10.1073/pnas.1009463108
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells facilitate the nuclear accumulation of inducible cAMP early repressor (ICER) and suppress nuclear factor of activated T cell c1 (NFATc1)

Abstract: Inducible cAMP early repressor (ICER) is a transcriptional repressor, which, because of alternate promoter use, is generated from the 3′ region of the cAMP response modulator (Crem) gene. Its expression and nuclear occurrence are elevated by high cAMP levels in naturally occurring regulatory T cells (nTregs). Using two mouse models, we demonstrate that nTregs control the cellular localization of ICER/CREM, and thereby inhibit IL-2 synthesis in conventional CD4 + T cells. Ablation of nTregs in depletion of regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(89 citation statements)
references
References 24 publications
(31 reference statements)
6
83
0
Order By: Relevance
“…If Treg were functionally impaired, an increase in IL-2 production should be evident. Indeed, when Treg are completely depleted, 10 times more IL-2 is secreted (25,26). The similar low amount of IL-2 produced from suppressed effector T cells in both genotypes of mice revealed functional equivalence between WT and NFAT2-deficient nTreg (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…If Treg were functionally impaired, an increase in IL-2 production should be evident. Indeed, when Treg are completely depleted, 10 times more IL-2 is secreted (25,26). The similar low amount of IL-2 produced from suppressed effector T cells in both genotypes of mice revealed functional equivalence between WT and NFAT2-deficient nTreg (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous results indicate that PGE 2 may exert direct effects on downregulation of CCR5 expression in human peripheral blood monocytes (Figure 2). These preliminary studies suggest that in addition to ICER-mediated down regulation of interleukin 2 (IL-2) in autoreactive CD4 + conventional T cells (Tcons) [5][6][7] ICER could also transcriptionally attenuate expression of CCR5 receptor in the presence of PGE 2 ( Figure 2). Therefore genomewide analysis of the pulse treatment of dmPGE 2 for Tregs, Tcons, and HSCs and their consequent CCR5 downregulation along with downregulation of other chemokines and chemokine receptors (such as CXCR4) will be informative.…”
Section: Unresolved Questions Of Pge 2 -Mediated Down Regulation Of Ccr5mentioning
confidence: 99%
“…Analogous effect could be achieved by direct activation of adenylyl cyclase (AC) by forskolin or inhibition of phosphodiesterases (PDEs) responsible for degradation of cAMP e.g. by Rolipram [6,7]. In response to cAMP/PKA, ICER is induced (after 2-4 h of delay, necessary for ICER synthesis) in the Foxp3 neg Tcons and later ICER protein is enforced to the nucleus in response to cAMP/PKA where it may attenuate CCR5 expression in cAMP dependent fashion (Figure 2).…”
Section: Mini Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Inter alia, during nTreg-mediated suppression we have shown that ICER preferentially inhibits the production of IL-2, an essential growth factor for auto-reactive Tcons [14]. We have recently shown that the transcription factors (TFs) ICER and nuclear factor of activated T cell c1 (NFATc1) are decisively involved in the suppression of CD4 + T cells by nTregs [15]. Deficiency in these TFs led to a resistance of CD4 + T cells against nTreg cell-mediated suppression [16].…”
mentioning
confidence: 99%